Design of an interface circuit for an electronic stethoscope - 208494 Asri Mokhtar; Fakulti Kejuruteraan Elektrik (Kuala Lumpur : Universiti Teknologi Malaysia, 1979)
Project Paper (Bachelor in Electrical Engineering) - Universiti Teknologi Malaysia, 1979